Waqf and its issues in Malaysia / Dahlia Ibrahim...[et al.] - Ibrahim, Dahlia; Mohamed Isa, Zuraidah; Ali, Norhidayah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2018)
Waqf is known as one of the Islamic trusts where its objective is to help the needy society. The concept of waqf is widespread in all part of the world, especially in Muslim countries such as Bangladesh, Pakistan, Indonesia, Brunei, and Malaysia. At present, topics on waqf become topics of interest to many Fiqh scholars as well as practitioners and academicians. Its concept has come to existence many years ago where its history can be traced from the 19th of century Ottoman Era. The application of the waqf system during the Ottoman Era has shed lights on how waqf can benefit the society through its proper implementation. Nevertheless, the lack of knowledge of the waqf concept among modern society can be detrimental to waqf’s potential in improving a society’s well-being. Therefore, it is essential that the concept of waqf be explored as to educate the society of its importance. For this reason, this paper intends to delve into the waqf concept, its characteristics, the structure of waqf management and some issues pertinent to its administration specifically in Malaysia.